Estimates of Labor-Supply Elasticities with Joint Borrowing Constraints of Couples - Jan Hendrik Gravert; Christian Bredemeier; Falko Jüßen (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Estimates of Frisch labor-supply elasticities are larger for women than for men. We show that standard labor-supply regressions tend to overestimate this gender difference. In couples with joint borrowing constraints, wage-rate fluctuations of the secondary earner are less important for the couples willingness to borrow. This results in smaller estimation biases for secondary earners which are mostly women, empirically. Quantitatively, our results suggest that the gender difference in true Frisch elasticities is about a fifth smaller than reported reviously.
Keywords: E24; J16; J22; 330